A Novel Modulator of the Renin–Angiotensin System, Benzoylaconitine, Attenuates Hypertension by Targeting ACE/ACE2 in Enhancing Vasodilation and Alleviating Vascular Inflammation - Zhang, Qi-Qiang; Chen, Feng-Hua; Wang, Fei; Di, Xue-Mei; Li, Wei; Zhang, Hai (Frontiers in Pharmacology, 2022)
The monoester alkaloids in Aconitum carmichaelii, including benzoylaconitine (BAC), benzoylmesaconine and benzoylhypaconitine, were found to have anti-hypertensive effects in spontaneously hypertensive rats (SHRs), of which BAC is the strongest. However, its antihypertensive target and underlying molecular mechanisms remain unclear. In this study, first, we screened the antihypertensive targets of BAC by using the CVDPlatform (www.cbligand.org/CVD) and found that ACE/ACE2 are the most possible targets. Then we verified the effect of BAC on ACE/ACE2 by virtual docking, SPR, enzyme activity assay and HUVECs cell experiment. And we found that BAC could bind with ACE/ACE2, inhibit ACE activity and protein expression, and activate ACE2 enzyme activity. Using vascular function test in vitro, we found that BAC could target ACE/ACE2 to enhance endothelium-dependent vasorelaxation. In BAC-treated SHRs, the levels of ACE and AngII in serum were reduced while Ang (1-7) was increased significantly, and the expression of ACE reduced, which suggested that BAC can inhibit ACE and activate ACE2 to inhibit AngI to AngII and promote AngII to Ang (1-7) to inhibit vasoconstriction and finally attenuate hypertension. Furtherly, the signaling pathways with regard to vasorelaxation and vascular inflammation were investigated. The results showed that BAC could significantly activate Akt/eNOS, increase NO production and promote endothelial related vasodilation; BAC could also reduce inflammatory factor TNF-α, IL6, inhibition of COX-2 expression, IKB-α phosphorylation to reduce vascular inflammation in SHRs. In brief, BAC targets ACE/ACE2 to enhance endothelium-dependent vasorelaxation and reduce vascular inflammation to attenuate hypertension as a potential modulator of renin-angiotensin system.